PENGARUH KEUANGAN DAERAH TERHADAP BELANJA MODAL KABUPATEN/KOTA DI PROVINSI KEPULAUAN BANGKA BELITUNG - Royda, Royda (Universitas Muhammadiyah Palembang, 2016)
Purpose - The research problem was how fiscal capacity influenced capital expenditure in Bangka Belitung Design/methodology - The analysis period was ten years starting from 2004 to 2013. The data analysis method used is descriptive analysis. The data were analyzed by using multiple regression model with Least Squares method.Findings – The results showed that the overall fiscal capacity significantly affected the capital expenditures by the coefficient of determination 83.33 percent. It was due to the fact that regional governments in Bangka Belitung had not been optimally allocating locally-generated revenues to finance regional expenditures, thus providing less stimulus for economic growth and being highly dependent on the transfer of funds from the central government.